Integrating Gamification in Multicultural Classrooms A Study on Enhancing Collaborative Learning and Cultural Empathy - Sari, Rini Kartika; Pratama, Andi (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
In multicultural classrooms, fostering collaborative learning and cultural empathy is critical to promoting inclusivity and effective education. This study investigates the application of a gamified framework to enhance these dimensions in diverse educational settings. The proposed framework integrates key game elements such as point systems, leaderboards, and role-playing activities to engage students and facilitate cross-cultural interactions. A mixed-methods approach was employed, involving 120 students across four multicultural classrooms. Quantitative results demonstrated significant improvements in collaboration and cultural empathy, with mean scores increasing from 3.2/5 to 4.1/5 and 3.0/5 to 4.0/5, respectively. Qualitative findings revealed that gamification fostered active participation, deeper cultural understanding, and inclusive learning experiences. Challenges included balancing competition with collaboration and ensuring effective teacher facilitation. This research contributes to the growing field of gamification in education, providing a scalable and adaptable framework for multicultural classrooms. The findings highlight gamification's potential to transform educational practices, fostering a collaborative and empathetic environment that embraces cultural diversity.